2020
DOI: 10.1088/2053-1591/ab87d5
|View full text |Cite
|
Sign up to set email alerts
|

PVA assisted ZnO based mesoporous ternary metal oxides nanomaterials: synthesis, optimization, and evaluation of antibacterial activity

Abstract: The poly (vinyl alcohol) (PVA) assisted highly mesoporous Zn-Fe-Mn oxides nanomaterials were synthesized using the sol-gel followed by the self-propagation techniques. The UV-vis spectroscopic technique was used to study the optical properties of the materials. The presence of metal-oxygen bond and deposited OH − /H 2 O species were characterized by FT-IR spectroscopic technique. The porous morphology and elemental analysis were confirmed by the SEM/EDX and further morphological and crystal structure studies w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 43 publications
1
20
0
Order By: Relevance
“…The ROS generation and electrostatic force interaction were suggested to be the probable antibacterial mechanism that led to bacterial death. Compared to single ZnO, the antibacterial bacterial activity of PVA assisted binary ZnO/Fe 2 O 3 and ZnO/Mn 2 O 3 [ 72 ] and ternary ZnO/Fe 2 O 3 /Mn 2 O 3 nanocomposite [ 20 ] also confirmed on the author’s earlier work. The nanocomposite materials were synthesized using the sol-gel followed by the self-propagation technique.…”
Section: Introductionmentioning
confidence: 56%
See 1 more Smart Citation
“…The ROS generation and electrostatic force interaction were suggested to be the probable antibacterial mechanism that led to bacterial death. Compared to single ZnO, the antibacterial bacterial activity of PVA assisted binary ZnO/Fe 2 O 3 and ZnO/Mn 2 O 3 [ 72 ] and ternary ZnO/Fe 2 O 3 /Mn 2 O 3 nanocomposite [ 20 ] also confirmed on the author’s earlier work. The nanocomposite materials were synthesized using the sol-gel followed by the self-propagation technique.…”
Section: Introductionmentioning
confidence: 56%
“…Yet, the antibacterial activity of ZnO is highly dependent on the particle size. It was reported that decreasing the particle size results in enhancing the antibacterial activity of ZnO [ 5 , 20 ]. To indicate, Jones et al compared the antibacterial activities of MgO, TiO 2 , Al 2 O 3 , CuO, CeO 2 , and ZnO against S. aureus RN6390 bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…The material synthesized using nitrate as a precursor is creating greater self-propagation process, so small particle size founding. The conducted amount of PVA loading and precursor's percentage optimization study was also reported earlier [19].…”
Section: Resultsmentioning
confidence: 80%
“…Through aging the formed sol for two days, the gel was dried at ∼110°C for about 13 h and calcined at ∼500°C for 3 h to form metal oxides. The detailed synthetic procedure is depicted in [19] and figure 1. The synthesized TMONCs were coded as TMOM1 and TMOM2 for TMONCs synthesized using sol-gel and co-precipitation methods without PVA, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The instrumental details and the reagents used were present as supplementary material (S). The detailed ZnO and PTMO-NCM synthesis procedures were also present in the author's earlier works [1,[26][27][28]. Roughly, the PVA polymer was dissolved in distilled water with continuous stirring on a magnetic stirrer at ~ 115 °C for about 15 min.…”
Section: Methodsmentioning
confidence: 99%